Application for the Rights of Children from Siri Marriages at the Religious Court of Lampung Province and its Implications for Legal Certainty - Rona Ayu Edithya Margareth; Muhammad Ismail Alfaruqy (SMART: Journal of Sharia, Traditon, and Modernity, 2025)
This article analyzes the legal certainty of the results of the ruling of the Lampung Province Religious Court in the case of the application for the rights of children from unregistered marriages after the Constitutional Court's ruling. The Constitutional Court's ruling nevertheless leaves problems in its implementation. The purpose of this article is to analyzeapplication for the rights of children from unregistered marriages following the Constitutional Court's decisionat the Lampung Provincial Religious Court and its implications for legal certainty for children. The method used is qualitative; empirical normative analysis approach, analysis with maslahah theory; data sources are obtained from the results of the determination of judges of three Religious Courts of Lampung Province. The results of the study show that the application for the rights of children from unregistered marriages was granted by the judge. The judge's legal ijtihad is in accordance with Islamic principles, namely for the benefit of the child (maqasyid as-syari’ah). The legal basis used in the jurisprudence of the Constitutional Court's decision Number 46/PUU-VII/2010. The implications of the determination of the three Religious Courts of Lampung Province provide legal certainty for children resulting from unregistered marriages, through the mechanism Isbat nikah.